Comparison of COVID-19 Medical Waste Management Strategies For Hospitals in Developed and Developing Country - Atikah Nadiah Syafei; Suyud Warno Utomo (Jurnal KESANS : Kesehatan dan Sains, 2022)
Introduction: The COVID-19 pandemic has not only caused a health emergency but also an emergency for medical waste, which as the number of COVID-19 infections increases, the generation of medical waste will also increase. Objective: This article aims to find out the pattern of handling COVID-19 B3 medical waste from hospitals in developed and developing countries. Method: This article is a systematic review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) model. Results and Discussion: There are 13 articles that analyze to find out the management of COVID-19 medical waste originating from hospitals from developing countries as well as developed countries. There are some similarities and differences in decision-making regarding COVID-19 waste treatment. Conclusions: Some countries are still adopting waste regulations in the pre-COVID-19 period. The thermal method of exterminating waste is still the best way to be chosen. However, the use of the incinerator method in some developing countries is still small